the Civil War - Perritano John 1950- (Scholastic. ; New York : ., 2012)
Presents the Civil War, including the siege of Petersburg, the fall of Atlanta, the battle of Franklin, and more.
The final phase begins -- Hope fades for the South -- The Tennessee campaign -- Sherman's southern campaign -- The Civil War ends.
Resource Links, April 2012
Includes bibliographical references (p. 47) and index.
6.2
5-8
Keywords: United States -- History -- Civil War, 1861-1865 -- Juvenile literature; United States -- History -- Civil War, 1861-1865 -- Campaigns -- Juvenile literature; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- 1861-1865, Civil War; United States -- History -- 1861-1865, Civil War -- Campaigns